2015
DOI: 10.1002/2015jc011083
|View full text |Cite
|
Sign up to set email alerts
|

Zonal jets in equilibrating baroclinic instability on the polar beta‐plane: Experiments with altimetry

Abstract: Results from the laboratory experiments on the evolution of baroclinically unstable flows generated in a rotating tank with topographic -effect are presented.We study zonal jets of alternating direction which occur in these flows. The primary system we model includes lighter fluid in the South and heavier fluid in the North with resulting slow meridional circulation and fast mean zonal motion. In a two-layer system the velocity shear between the layers results in baroclinic instability which equilibrates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…(2004, 2007) alternatively used a specific convective forcing by spraying dense (salt) water at the free surface of a fresh water layer, and in a similar fashion, Afanasyev et al. (2012), Slavin & Afanasyev (2012), Zhang & Afanasyev (2014), Matulka & Afanasyev (2015) performed a localized forcing involving sources of buoyancy. Another method, which has the advantage of allowing a close control of the location, scale and intensity of the forcing, consists in applying a mechanical forcing, provided that, again, it does not directly force the mean flow.…”
Section: Introductionmentioning
confidence: 99%
“…(2004, 2007) alternatively used a specific convective forcing by spraying dense (salt) water at the free surface of a fresh water layer, and in a similar fashion, Afanasyev et al. (2012), Slavin & Afanasyev (2012), Zhang & Afanasyev (2014), Matulka & Afanasyev (2015) performed a localized forcing involving sources of buoyancy. Another method, which has the advantage of allowing a close control of the location, scale and intensity of the forcing, consists in applying a mechanical forcing, provided that, again, it does not directly force the mean flow.…”
Section: Introductionmentioning
confidence: 99%
“…A classic model for a baroclinically unstable system is a rotating annulus where heating/cooling is provided at the outer wall/centre of the tank respectively. Different aspects of the dynamics of this system were studied in a number of experiments (Hide and Mason, 1975;Mason, 1975;Read, 1997, 1998;Wordsworth et al, 2008;Smith et al, 2014 Matulka and Afanasyev (2015). It was shown that the meridional scale of the jets is determined to a large extent by the radius of deformation and, at the same time, is in good agreement with the Rhines scale (Rhines, 1975).…”
Section: Introductionmentioning
confidence: 66%
“…The radial motion, in turn, causes zonal circulation. Measurements of barotropic and baroclinic components of velocity (for details see Matulka and Afanasyev, 2015) show that the upper layer rotates cyclonically while the lower layer rotates anticyclonically. The shear between the layers makes the system baroclinically unstable.…”
Section: General Flow Evolutionmentioning
confidence: 99%
See 2 more Smart Citations